2009
DOI: 10.1111/j.1365-2621.2007.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of acid‐adapted or non‐adapted Salmonella Enteritidis, Listeria monocytogenes and Escherichia coli O157:H7, in traditional Greek salads

Abstract: The fate of three pathogens Salmonella Enteritidis, Listeria monocytogenes and Escherichia coli O157:H7 that were inoculated in fish roe salad and aubergine salad with or without preservatives after being adapted in acid environment or not, was determined. The salads were stored at 10°C and the pathogens population was counted at regular intervals. Parameters (lag time, death rates calculated with Baranyi equation) were used to compare the behaviour of the pathogens. In the absence of preservatives the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
1
12
0
1
Order By: Relevance
“…This can be used in agriculture in the control of larvae and the eggs of the wax moths, since it destroys the wax combs [59,60]. Other studies suggest useful effects against pathogens in a variety of food products such as moutable (eggplant dip) [61,62], salads [63,64], hummus [65], and tahini [66,67]. Other essential components such as eicosane, palmitic acid, and oleic acid found in this study in both species have also been reported in studies of jatropha.…”
Section: Discussionsupporting
confidence: 76%
“…This can be used in agriculture in the control of larvae and the eggs of the wax moths, since it destroys the wax combs [59,60]. Other studies suggest useful effects against pathogens in a variety of food products such as moutable (eggplant dip) [61,62], salads [63,64], hummus [65], and tahini [66,67]. Other essential components such as eicosane, palmitic acid, and oleic acid found in this study in both species have also been reported in studies of jatropha.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies evaluating the effects of pH and storage conditions on survival of foodborne pathogens in eggplant dip have used recipes based on mayonnaise containing garlic (Skandamis and Nychas, 2000;Tassou et al, 2009 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…After 7 d storage at this temperature, the pH values decreased in samples with 0, 0.4, 0.6 and 0.8% citric acid from 5.respectively. Previous studies on the effects of storage temperature and pH on the survival and growth of foodborne pathogens in salad/dip such as non-tahini-based eggplant salad and tahini-based products such as hummus dip (cooked, mashed chickpeas blended with tahini, lemon juice, garlic and salt) were found in the literature(Skandamis and Nychas, 2000;Tassou et al, 2009;Al-Holy et al 2006;Alali et al 2012). These studies also found that the survival and growth of foodborne pathogens in these products depended on intrinsic (e.g.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…EnteritidisMayonnaiseoil oregano essential oils (OEO1/OEO2) Nisin EDTAAntimicrobial activity of OEO against S. Enteritidis was improved when combined with nisin or EDTA.[74]U.K, S. EnteritidisMayonnaisegarlicGarlic (1%) reduced the viable cells of S. Enteritidis in mayonnaise by a factor of 10.[67]Greece S . EnteritidisMayonnais- based Aubergine saladsorbic/benzoic acidsAddition of preservatives decreased the pathogen survival.[83]U.K. S . EnteritidisMayonnaisepHWithin the pH 4.2–4.5 S .…”
Section: Table A1mentioning
confidence: 99%